Complement inhibition by hydroxychloroquine prevents placental and fetal brain abnormalities in antiphospholipid syndrome. (December 2016) - Bertolaccini, Maria Laura; Contento, Gregorio; Lennen, Ross; Sanna, Giovanni; Blower, Philip J.; Ma, Michelle T.; Sunassee, Kavitha; Girardi, Guillermina
Abstract: Placental ischemic disease and adverse pregnancy outcomes are frequently observed in patients with antiphospholipid syndrome (APS). Despite the administration of conventional antithrombotic treatment a significant number of women continue to experience adverse pregnancy outcomes, with uncertain prevention and management. Efforts to develop effective pharmacological strategies for refractory obstetric APS cases will be of significant clinical benefit for both mothers and fetuses. Although the antimalarial drug, hydroxychloroquine (HCQ) is increasingly used to treat pregnant women with APS, little is known about its efficacy and mechanism of action of HCQ. Because complement activation plays a crucial and causative role in placental ischemia and abnormal fetal brain development in APS we hypothesised that HCQ prevents these pregnancy complications through inhibition of complement activation. Using a mouse model of obstetric APS that closely resembles the clinical condition, we found that HCQ prevented fetal death and the placental metabolic changes -measured by proton magnetic resonance spectroscopy in APS-mice. Using 111 In labelled antiphospholipid antibodies (aPL) we identified the placenta and the fetal brain as the main organ targets in APS-mice. Using this same method, we found that HCQ does not inhibit aPL binding to tissues as was previously suggested from in vitro studies. While HCQ did not affect aPL binding to fetal brain it prevented fetal brain abnormal cortical development. HCQ prevented complement activation in vivo and in vitro . Complement C5a levels in serum samples from APS patients and APS-mice were lower after treatment with HCQ while the antibodies titres remained unchanged. HCQ prevented not only placental insufficiency but also abnormal fetal brain development in APS. By inhibiting complement activation, HCQ might also be an effective antithrombotic therapy. Highlights: A new mouse model of obstetric APS that resembles more closely the clinical scenario was developed. aPL antibodies induce metabolic changes in placenta and fetal brain measured by proton magnetic resonance spectroscopy. Using radiolabeled aPL antibodies and SPECT/CT the placenta and fetal brain were identified as target organs in APS in vivo . Hydroxychloroquine (HCQ) prevents placental and neurodevelopmental abnormalities in APS. HCQ inhibits complement in vitro and in vivo .